2015
DOI: 10.5194/bg-12-2995-2015
|View full text |Cite
|
Sign up to set email alerts
|

Imaging tropical peatlands in Indonesia using ground-penetrating radar (GPR) and electrical resistivity imaging (ERI): implications for carbon stock estimates and peat soil characterization

Abstract: Abstract. Current estimates of carbon (C) storage in peatland systems worldwide indicate that tropical peatlands comprise about 15 % of the global peat carbon pool. Such estimates are uncertain due to data gaps regarding organic peat soil thickness, volume and C content. We combined a set of indirect geophysical methods (ground-penetrating radar, GPR, and electrical resistivity imaging, ERI) with direct observations using core sampling and C analysis to determine how geophysical imaging may enhance traditional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 27 publications
6
47
1
1
Order By: Relevance
“…These laboratory tests have not been explicitly confirmed by the field surveys presented in this paper. This results probably from the spatial variability of the peatland and influence of individual factors (such as moisture content, ash The ERI method may be useful for determining the stratigraphic contact between the peat layer and the mineral substrate (Slater and Reeve 2002;Comas et al 2015;Walter et al 2016), which is also confirmed by this report.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These laboratory tests have not been explicitly confirmed by the field surveys presented in this paper. This results probably from the spatial variability of the peatland and influence of individual factors (such as moisture content, ash The ERI method may be useful for determining the stratigraphic contact between the peat layer and the mineral substrate (Slater and Reeve 2002;Comas et al 2015;Walter et al 2016), which is also confirmed by this report.…”
Section: Discussionsupporting
confidence: 82%
“…Detailed information from the GPR survey (Kowalczyk et al 2014) would be very difficult to obtain using data solely from the drillings. The potential of GPR and ERI for estimating peat thickness was confirmed by Comas et al (2015). However, these researchers indicate the limitations of geophysical methods in determining the thickness of the peat.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The study of peat soil has developed rapidly to be able to determine carbon emissions, especially in the peatlands of Indonesia [1][2][3][4][5][6][7]. A large amount of carbon emission is produced by peatlands, which is mostly determined by the depth or the thickness of the peat [1,2,8].…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of carbon emission is produced by peatlands, which is mostly determined by the depth or the thickness of the peat [1,2,8]. Accurate information parameters on the depth and the thickness of the peat must be used in this research.…”
Section: Introductionmentioning
confidence: 99%